10+w=-w-10

Simple and best practice solution for 10+w=-w-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+w=-w-10 equation:


Simplifying
10 + w = -1w + -10

Reorder the terms:
10 + w = -10 + -1w

Solving
10 + w = -10 + -1w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add 'w' to each side of the equation.
10 + w + w = -10 + -1w + w

Combine like terms: w + w = 2w
10 + 2w = -10 + -1w + w

Combine like terms: -1w + w = 0
10 + 2w = -10 + 0
10 + 2w = -10

Add '-10' to each side of the equation.
10 + -10 + 2w = -10 + -10

Combine like terms: 10 + -10 = 0
0 + 2w = -10 + -10
2w = -10 + -10

Combine like terms: -10 + -10 = -20
2w = -20

Divide each side by '2'.
w = -10

Simplifying
w = -10

See similar equations:

| (1+1+.92+.83)*X=18.75 | | Sin(2x+15)=Cos(3x) | | 3/4x-Y=4 | | 3(m-12)=20 | | ln(37)=.67ln(x)+3.37 | | (1+1+.92+83)*X=18.75 | | 2a-2+6-4a= | | -4h=8-8h | | 20x(3/10) | | -9y+10=-7y-10 | | 2f-6=7s-3 | | -9+6g=-4+7g | | 105*12=16a | | 5y=13-4x | | 14-2a=4a | | 5y/6-2=1-2y/3 | | (x+10)*2=2y-62 | | 9z=-6+6z | | 5x^5+2= | | x+6(-2.2)=27 | | -7b=-5b-8b | | 6m=5m+9 | | (4a^2-9)=0 | | -6c=-5c-7 | | 17+5-7=10+2x+3x | | 3j-7=10j | | 36y^2=30y | | -7d=-6d-7 | | 3(15+6y)+2y=1 | | 14sinx=0.236127203 | | 5x+9=3+15 | | 5y+3y-6y-y=11 |

Equations solver categories